Stakeholder Participation in Multilevel Governance of Maritime Transportation Development through Special Autonomy Funds in Southwest Papua Province - Salossa, Viktor Fransiskus; Ibrahim, Muhammad Akmal; Musa'ad, Muhammad (KnE Social Sciences, 2025)
The development of sea transportation through special autonomy funds is very important to reduce the development gap in the eastern region of Indonesia. In order for the development of sea transportation to be successful effectively, support and participation of various stakeholders are needed in the process. This study aims to explore stakeholder participation in multiLevel governance in the development of sea transportation through special autonomy funds in South Sorong Regency and Maybrat Regency, Southwest Papua Province. This study uses a qualitative approach. Data collection includes observation, in-depth interviews, and documentation. The research informants include officials from the central government, the West Papua Provincial Government, the South Sorong and Maybrat Regency Governments, as well as representatives from the local community and the private sector. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the study indicate that stakeholder participation is relatively low and needs to be increased in the process of developing marine transportation based on multilevel governance, especially from the community and private sector. So far, the government as a policymaker has not involved the community and private sector in decisionmaking, so that the government’s role is too dominant. In addition, it was found that the government is less transparent and accountable in terms of the process and stages of marine transportation development toward the community and private sector so that supervision of both parties in the process of developing marine transportation carried out by the government is very limited, the community and private sector should be involved in the entire decision-making process and can access information regarding marine transportation development.